Effect of agro industrial wastes compost on soil health and onion yields improvements: Study at field condition - Feyisa Girma Erana; Tesfaye Alemu Tenkegna; Seyoum Leta Asfaw (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Industries are generating numerous amount and types of organic wastes to the environment. The aim of the present study was to investigate the effects of agro industrial wastes compost on soil physicochemical quality, soil microbial population, growth and yield of onion (Allium cepa L.) under field condition. Method The experiment was conducted in a completely randomized plot design at field condition. Allium cepa L. was grown using five different levels of agro industrial wastes compost, three different levels of inorganic fertilizers and three controls. Results Compost amendment improved the soil pH, TOC, TKN, field capacity (FC), permanent wilting point (PWP), and available water content (AWC), cultivable bacterial count and fungi. But no significant effect was found on electrical conductivity (EC), available phosphorus (P) compared to the control. Exchangeable Na, K, Ca, Mg, Fe, Zn, and Cu increased while Pb, Cr, and Mn value showed no significant change with compost application. Field application of compost improved onion shoot numbers, shoot girth, and shoot length. Further, significant shoot weight and bulb weight were also obtained after compost treatment. Conclusion After compost amendment significant improvement in soil fertility and onion yield was obtained. This can be recommended for small scale farmerâs food security improvement and combined with agro industrial wastes management.